The Utility of Ocular Imaging in Traumatic Optic Nerve Avulsion: A Case Report - ikhwanuliman Putera; Syntia Nusanti; Nur Aisyah Rahmawati; Annisa Nindiana Pertiwi; Mario Marbungaran Hutapea (Majalah Oftalmologi Indonesia, 2022)
Objective: To describe a detailed presentation and the utility of ocular imaging, both ocular ultrasound and orbital computed tomography (CT), to confirm the diagnosis of traumatic ONA in which megadose steroid would give no advantage. Case Presentation: A five-year-old boy came with a unilateral sudden visual loss after incidentally falling with his left eye struck to a handlebar of a parked bicycle. His left eye had no light perception, ophthalmoplegia, and showing 4+ relative afferent pupillary defect. A hallmark "pit" sign and a pale retina without a tear were noted. B-scan ocular ultrasound displayed retinal step sign, vitreous hemorrhage in front of the optic canal, lamina cribrosa defect, edematous retina, and retracted optic nerve. Orbital computed tomography scan showed a disruption of the optic nerve-globe junction. Steroid infusion was decided not to be given. Conclusion: Ocular imaging, especially ultrasound, along with a thorough examination, is satisfactorily adequate to confirm the diagnosis of traumatic ONA.